2021
DOI: 10.1371/journal.pone.0243645
|View full text |Cite
|
Sign up to set email alerts
|

Transfection methods for high-throughput cellular assays of voltage-gated calcium and sodium channels involved in pain

Abstract: Chemical transfection is broadly used to transiently transfect mammalian cells, although often associated with cellular stress and membrane instability, which imposes challenges for most cellular assays, including high-throughput (HT) assays. In the current study, we compared the effectiveness of calcium phosphate, FuGENE and Lipofectamine 3000 to transiently express two key voltage-gated ion channels critical in pain pathways, CaV2.2 and NaV1.7. The expression and function of these channels were validated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The Na V 1.1/K V 2.1 chimera was subcloned into the mammalian vector pCDNA3.1 and new constructs confirmed by DNA sequencing. Plasmid constructs were used to transfect HEK293 cells using the FuGENE reagent as previously described ( Hasan et al, 2020 ). Briefly, HEK293 cells were transfected with 18 μg DNA using a ration of DNA:FuGENE at 1:3 and transfection media replaced with fresh media after 16 h incubation at 37°C 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The Na V 1.1/K V 2.1 chimera was subcloned into the mammalian vector pCDNA3.1 and new constructs confirmed by DNA sequencing. Plasmid constructs were used to transfect HEK293 cells using the FuGENE reagent as previously described ( Hasan et al, 2020 ). Briefly, HEK293 cells were transfected with 18 μg DNA using a ration of DNA:FuGENE at 1:3 and transfection media replaced with fresh media after 16 h incubation at 37°C 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were transfected with ASOs using lipofectamine; the transfection mechanism was the formation of cationic liposomes that enabled the internalization of anionic ASOs. Then, in contact with the cell membrane, liposomes created endosomes to enter the cell [ 185 ]. The innovative in silico tool they proposed for ASO design succeeded in targeting different regions of the viral genome and reduced the viral yield and infection.…”
Section: The Landscape Of Nucleic Acid-based Therapies In Sars-cov-2mentioning
confidence: 99%
“…Cells were transfected using FuGENE, a cationic polymer that creates complexes with anionic ASOs. The complexes could create endosomes in the cell membrane to penetrate the cell [ 185 , 189 ]. Even though ASOs have been demonstrated to be efficient and specific in targeting SARS-CoV-2 in vitro and in vivo, further experiments are needed to confirm their potential use as therapeutic agents in humans against SARS-CoV-2.…”
Section: The Landscape Of Nucleic Acid-based Therapies In Sars-cov-2mentioning
confidence: 99%
“…Here, the opening ratio of the former was obtained from steady-state activation analysis, while that of the latter was obtained from both steady-state activation and inactivation analyses (see also Analysis of Whole-Cell Patch-Clamp Recordings subsection of the Experimental Procedures). Steady-state analysis of Na v in N2A cells was then performed to examine the effects of PUFAs, including AA (1), DGLA (5), EPA (6), and ETA (7) (Figure 4). It was found that the V a was −30.0 ± 0.7 mV, whereas the V h was −69.0 ± 0.2 mV.…”
Section: Steady-state Analysis Of Na V In N2a In the Presence Of Pufasmentioning
confidence: 99%